Thermal conductivity of compacted bentonite as a buffer material for a high-level radioactive waste repository. (August 2016) - Lee, Jae Owan; Choi, Heuijoo; Lee, Jong Youl
Highlights: The thermal conductivities were measured under various disposal conditions. They were significantly influenced by the water content and dry density. They were not sensitive to the temperature and the anisotropic structure. A new model of thermal conductivity was proposed for the thermal analysis. Abstract: Bentonite buffer is one of the major barrier components of a high-level radioactive waste (HLW) repository, and the thermal conductivity of the bentonite buffer is a key parameter for the thermal performance assessment of the HLW repository. This study measured the thermal conductivity of compacted bentonite as a buffer material and investigated its dependence upon various disposal conditions: the dry density, water content, anisotropic structure of the compacted bentonite, and temperature. The measurement results showed that the thermal conductivity was significantly influenced by the water content and dry density of the compacted bentonite, while there was not a significant variation with respect to the temperature. The anisotropy of the thermal conductivity had a negligible variation for an increasing dry density. The present study also proposed a geometric mean model of thermal conductivity which best fits the experimental data.